Report of the Council at the opening of the Twenty-second Session - SSISI (Statistical and Social Inquiry Society of Ireland, 1869)
The Council of this Society have now, at the commencement of the twenty-second session of its existence, to offer to you some account of its proceedings during the past year. In interest they compare not unfavourably with those of previous years, and show that the members are fully alive to the importance of discussing the great social and economic questions of the day at the meetings, so that the views of each may be corrected or confirmed by others who have devoted attention to the same subject.
Read Friday, 22nd January, 1869
Keywords: 314.15